Current Status of Mesenchymal Stem/Stromal Cells for Treatment of Neurological Diseases - Soares, Milena B. P.; Gonçalves, Renata G. J.; Vasques, Juliana F.; da Silva-Junior, Almir J.; Gubert, Fernanda; Santos, Girlaine Café; de Santana, Thaís Alves; Almeida Sampaio, Gabriela Louise; Silva, Daniela Nascimento; Dominici, Massimo; Mendez-Otero, Rosalia (Frontiers in Molecular Neuroscience, 2022)
Neurological disorders include a wide spectrum of clinical conditions affecting the central and peripheral nervous systems. For these conditions, which affect hundreds of millions of people worldwide, generally limited or no treatments are available, and cell-based therapies have been intensively investigated in preclinical and clinical studies. Among the available cell types, mesenchymal stem/stromal cells (MSCs) have been widely studied but as yet no cell-based treatment exists for a neurological disease. We review current knowledge of the therapeutic potential of MSC-based therapies for neurological diseases, as well as possible mechanisms of action that may be explored to hasten the development of new and effective treatments. We also discuss the challenges for culture conditions, quality control, and development of potency tests, aiming to generate more-efficient cell-therapy products for neurological disorders.